Time series classifier recommendation by a meta-learning approach. (August 2022) - Abanda, A.; Mori, U.; Lozano, Jose A.
Highlights: Time series classifier recommendation tackled for the first time in literature. Novel proposal of landmarkers for time series classification. Hierarchical inference of meta-targets analysed for the first time in a consistent way. Abstract: This work addresses time series classifier recommendation for the first time in the literature by considering several recommendation forms or meta-targets: classifier accuracies, complete ranking, top-M ranking, best set and best classifier. For this, an ad-hoc set of quick estimators of the accuracies of the candidate classifiers (landmarkers) are designed, which are used as predictors for the recommendation system. The performance of our recommender is compared with the performance of a standard method for non-sequential data and a set of baseline methods, which our method outperforms in 7 of the 9 considered scenarios. Since some meta-targets can be inferred from the predictions of other more fine-grained meta-targets, the last part of the work addresses the hierarchical inference of meta-targets. The experimentation suggests that, in many cases, a single model is sufficient to output many types of meta-targets with competitive results.